2016
DOI: 10.3354/ab00650
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in cusk eel sound production at a proposed US wind farm site

Abstract: Many marine organisms produce sound during key life history events. Identifying and tracking these sounds can reveal spatial and temporal patterns of species occurrence and behaviors. We describe the temporal patterns of striped cusk eel Ophidion marginatum calls across approximately 1 yr in Nantucket Sound, MA, USA, the location of a proposed offshore wind energy installation. Stereotyped calls typical of courtship and spawning were detected from April to October with clear diel, monthly, and seasonal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Most work on ophidiid sonic anatomy and sound production has utilized shallow-water species of the subfamily Ophidiinae (Rose, 1961;Courtenay, 1971;Sprague and Luczkovich, 2001;Parmentier et al, 2006aParmentier et al, , 2006bParmentier et al, , 2006cParmentier et al, , 2010Fine et al, 2007;Nguyen et al, 2008;Kever et al, 2014Kever et al, , 2015Mooney et al, 2016). Although conservative externally (Nielsen et al, 1999), various Ophidiinae species have a number of unusual morphological adaptations for sound production including antagonistic muscle pairs, a swimbladder that in some species secretes a lima-bean shaped rocker bone at its rostral end for sonic muscle attachment (Parmentier et al, 2008), and a neural arch above the first vertebra capable of pivoting in the rostral-caudal plane (Fine et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most work on ophidiid sonic anatomy and sound production has utilized shallow-water species of the subfamily Ophidiinae (Rose, 1961;Courtenay, 1971;Sprague and Luczkovich, 2001;Parmentier et al, 2006aParmentier et al, , 2006bParmentier et al, , 2006cParmentier et al, , 2010Fine et al, 2007;Nguyen et al, 2008;Kever et al, 2014Kever et al, , 2015Mooney et al, 2016). Although conservative externally (Nielsen et al, 1999), various Ophidiinae species have a number of unusual morphological adaptations for sound production including antagonistic muscle pairs, a swimbladder that in some species secretes a lima-bean shaped rocker bone at its rostral end for sonic muscle attachment (Parmentier et al, 2008), and a neural arch above the first vertebra capable of pivoting in the rostral-caudal plane (Fine et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Species with slow muscles produce a single pulse per contraction, and contraction rate does not determine frequency within a pulse (Fine et al, 2007;Parmentier et al, 2010Parmentier et al, , 2016Mok et al, 2011;Parmentier and Fine 2016). For instance the cusk-eel Ophidion marginatum (subfamily Ophidiinae) produces sounds composed of one to 27 pulses with a peak frequency of about 1200 Hz (Mann et al, 1997;Sprague and Luczkovich, 2001; Rountree and Bowers-Altman, 2002;Mooney et al, 2016). This peak frequency is too high to be produced by individual contractions of superfast sonic muscles, suggesting a slow-muscle mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…If such species are not widely or uniformly distributed, then their contribution to local soundscapes, and therefore potentially the applicability of that soundscape to estimate diversity, is limited to the detection range. By contrast, high-amplitude cetacean and fish signals generated in deeper water may propagate great distances and dominate soundscapes [ 54 , 193 , 194 ]. Initial soundscape studies showed differences between soundscapes separated by several kilometres [ 89 , 93 , 195 ], and more recent efforts have noted that reefs separated by just a few hundred metres may vary [ 149 ].…”
Section: Considerations For Using Acoustic Methods To Estimate Marinementioning
confidence: 99%
“…In recent years, passive acoustic monitoring has been used as a non‐invasive method to identify and monitor natural populations of fishes over long periods of time by using sound production as a reliable natural indicator to detect fish aggregation sites or to follow seasonal activities of soniferous species (Luczkovich et al ., ; Luczkovich, Mann & Rountree, ; Bertucci et al ., ). This method has thus become a useful tool for the study of protected fishes and appears valuable for conservation efforts as monitoring sound production may support investigating different aspects of the biology of fishes (Hernandez et al ., ; Montie, Vega & Powell, ; Ruppé et al ., ; Mooney et al ., ). However, these studies are generally restricted to narrow regions and are time restricted.…”
Section: Introductionmentioning
confidence: 97%